1990
DOI: 10.1002/chin.199015156
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Amino Acids as Chiral Building Blocks: Dihydrothiazole Derivatives (δ4‐Thiazoline) Made from Cysteine.

Abstract: Pivalaldehyde (I) reacts with L‐cysteine hydrochloride (II) to give the 1,3‐thiazolidinium chloride (III) which is N‐acylated with benzyl chloroformate (IV) to give (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In previous work, it was found that 1 :I cisltrans-mixtures of N-unsubstituted oxazolidines give preferentially the cis-products upon formylation and methoxycarbonylation [ 1 11 [ 141 [33]. Similarly, thiazolidines derived from cysteine were found to give exclusively the cis -products upon benzyloxycarbonylation [34]. The structural information from X-ray analyses was used to interpret this stereoselectivity [ 1 813).…”
mentioning
confidence: 94%
“…In previous work, it was found that 1 :I cisltrans-mixtures of N-unsubstituted oxazolidines give preferentially the cis-products upon formylation and methoxycarbonylation [ 1 11 [ 141 [33]. Similarly, thiazolidines derived from cysteine were found to give exclusively the cis -products upon benzyloxycarbonylation [34]. The structural information from X-ray analyses was used to interpret this stereoselectivity [ 1 813).…”
mentioning
confidence: 94%
“…Nongenetically coded amino acids, particularly non-natural α-amino acids, have contributed strongly in the area of peptide research. These amino acids play a significant role in peptide analogues to limit conformational flexibility, to enhance enzymatic stability, and to improve pharmacodynamics and bioavailability. Side chain conformational restrictions deliver a practical approach in peptidomimetics to understand the interactions of peptides with proteins, nucleic acids, lipids, and sugars in biological systems…”
mentioning
confidence: 99%
“…
~~~~

The X-ray structures of fifteen 1,3-imidazolidine, 1,3-oxazolidine, 1,3-dioxan-4-one, and hydropyrimidine-4( I H)-one derivatives are described ( Table 2) and compared with known structures of similar compounds (Figs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The differences between structures containing exocyclic N-acyl groups and those lacking this structural element arise from the A',' effect of the amide moieties.

…”
mentioning
confidence: 99%